The Application of Reminiscence Therapy in the Geriatrics - Yongmei, Hou (Disease and Health: Research Developments Vol. 3, 2025)
Background: Reminiscence Therapy (RT), as a psychological intervention method, is increasingly widely used in geriatrics. However, there are still some uncertainties about the implementation plan and effect evaluation. Objective: The objective of the study is to understand the progress of RT in geriatrics, and point out its shortcomings and development directions. Methods: Literature retrieval was used to search papers published in Chinese or English in the past five years, using six databases including CNKI, PubMed, PsychInfo, Embase, Cinahl, and Web of Science with the keywords "reminiscence therapy + elderly". Results: Twenty-six papers were included. RT can improve the cognitive function, and emotional and behavioral symptoms of the elderly, and enhance their quality of life. However, there is a lack of standardized guidelines for the duration, form, frequency, procedure, and effect evaluation, as well as a theoretical foundation and framework. Conclusion: It is necessary to combine national conditions and cultural backgrounds to carry out multi-center, large-sample experimental research, and strengthen long-term effect tracking research about RT.